Environmental Factors and Soil CO2 Emissions in an Alpine Swamp Meadow Ecosystem on the Tibetan Plateau in Response to Experimental Warming. (29th March 2016) - Wang, Bin; Niu, Ben; Yang, Xiaojie; Gu, Song
Abstract : We examined the response of soil CO2 emissions to warming and environmental control mechanisms in an alpine swamp meadow ecosystem on the Tibetan Plateau. Experimental warming treatments were performed in an alpine swamp meadow ecosystem using two open-top chambers (OTCs) 40 cm (OA) and 80 cm (OB) tall. The results indicate that temperatures were increased by 2.79°C in OA and 4.96°C in OB, that ecosystem CO2 efflux showed remarkable seasonal variations in the control (CK) and the two warming treatments, and that all three systems yielded peak values in August of 123.6, 142.3, and 166.2 g C m −2 month −1 . Annual CO2 efflux also showed a gradual upward trend with increased warming: OB (684.1 g C m −2 year −1 ) > OA (580.7 g C m −2 year −1 ) > CK (473.3 g C m −2 year −1 ). Path analysis revealed that the 5 cm depth soil temperature was the most important environmental factor affecting soil CO2 emissions in the three systems.